Effects of Heart Failure Therapies on Atrial Fibrillation: Biological and Clinical Perspectives - Alfredo Mauriello; Antonia Ascrizzi; Anna Selvaggia Roma; Riccardo Molinari; Alfredo Caturano; Egidio Imbalzano; Antonello D'Andrea; Vincenzo Russo (MDPI AG, 2024)
Heart failure (HF) and atrial fibrillation (AF) are prevalent cardiovascular diseases that contribute significantly to morbidity, mortality, hospitalisation, and healthcare costs. It is not uncommon for these conditions to coexist and have mutually reinforcing effects. A critical factor in the aetiology of these conditions is oxidative stress, driven by reactive oxygen species (ROS), which contributes to atrial remodelling and fibrosis. The recent introduction of new drugs for the treatment of heart failure has also had an impact on the management of atrial fibrillation due to their influence on oxidative stress. The objective of this review is to analyse the effects of these therapies, including their role in mitigating ROS, on the prevention and treatment of AF in HF patients.